Massive left atrial thrombus evades multimodality imaging as a myxoma in a bicaval heart transplant recipient. Issue 9 (5th July 2022) - Shou, Benjamin L.; Halub, Meghan E.; Zhou, Alice L.; Tompkins, Bryon A.; Choi, Chun W.
Abstract: Intracardiac masses are an extremely rare and poorly described complication following a bicaval heart transplantation. We describe the case of an asymptomatic 62‐year‐old male with a large left atrial mass found incidentally on transthoracic echocardiography 6 years post‐transplant. A battery of additional imaging tests was ordered including transesophageal echocardiography, 18 F‐fluorodeoxyglucose positron emission tomography/computed tomography, and T1 and T2 magnetic resonance imaging. Although imaging biomarkers were generally nonspecific, the mass was most consistent with a cardiac myxoma. However, intraoperative findings confirmed by pathology revealed a massive organizing thrombus. The patient had an uneventful recovery after surgical removal of the mass. Our case highlights a very rare phenomenon in heart transplant recipients which remains a unique diagnostic challenge even with current advances in imaging.